Determining Factors of Brand Loyalty on the Use of Social Media for Marketing with Brand Trust Playing a Mediating Role - Erwin Setiawan; Nugraha Saefudin (PT. Publikasiku Academic Solution, 2024)
The high level of social media use by Indonesian people has led companies to use it as a means of marketing communication for a brand. The study try to examine the direct and indirect impacts on brand loyalty of the use of social media for marketing activities through brand trust as a mediator. The method used associative research with a research sample of 150 customers of Cafe Kopi Salarea, Bandung. The study proves that there was a direct and indirect effect social media marketing on brand loyalty through brand trust. While content marketing hasn’t a direct effect but has an indirect effect through brand trust. The results expand on the findings of earlier research that are still rare and can be used to develop subsequent research models. Marketing through social media is an effective strategy for companies to increase brand trust and brand loyalty. The findings of this study highlight the significant role of social media marketing in fostering brand loyalty, both directly and indirectly through brand trust. While content marketing does not have a direct effect on brand loyalty, its influence is mediated effectively by brand trust. These results emphasize the importance of social media as an impactful marketing strategy for enhancing brand trust and loyalty, providing valuable insights for companies aiming to strengthen their brand positioning in the digital era.